Code of silence: sexual misconduct by Federal judges, the secret system that protects them, and the women who blew the whistle - Olsen, Lise (Beacon Press, 2021)
An awkward encounter -- Flight -- Kings of the courts -- Chambers and secrets --The reluctant whistleblower -- The complaint -- Her Honor -- A botched investigation -- Interlude the exposé -- A corrupt judge -- The keeper of secrets -- A criminal probe -- Person B -- The path to impeachment -- Another encounter with Judge Kozinski -- Calls for reform-and a backlash.